Epidemioclinical, Therapeutic and Prognostic Features of Tropical Endemic Limbo-Conjunctivitis (TELC) at the Yopougon University Hospital: A Report About 150 Cases Collected - Sowagnon, T Y C; Kouassi-Rebours, A. C.; Kouaï, B T E; Koné, K.; Appia, G B; Kouassi, F X; Koné, S (Transactions on Engineering and Computing Sciences, 2023)
Introduction: Tropical Endemic Limbo-Conjunctivitis is a common and chronic affection of the subject of less than 15 years, which results in the inflammation of the conjunctiva and the limbus with the possibility of extension to the cornea in its advanced forms. The objective of our study was to determine the epidemioclinical and therapeutic features of this affection and to assess its visual functional prognosis. Patients and Methods: This was a retrospective study that was carried out in the Ophthalmology department of the Yopougon University Hospital from July 2021 to September 2021. It focussed on 150 cases of Tropical endemic Limbo-Conjunctivitis which received treatment. We analysed the epidemioclinical, therapeutic and prognostic features from medical records. Results: The average age of our patients was 5.22 years with extremes of 7 months and 12 years. The male gender predominated with a sex ratio of 1.53. Our patients were in the majority of cases subject to multi-allergic manifestations (asthma, rhinitis, atopic dermatitis). Stage I of the Diallo classification was the most common clinical form in consultation. The treatment most often associated ocular washing with a topical antihistamine and/or antibiocorticoid. The outcome was marked by a remission in the majority of cases with however cases of recurrence occurring at variable times. Discussion: Limbo-conjunctivitis is an allergic pathology which mainly affects male subjects in a hot and dry environment. It is common in children under five years and regresses with age. Conclusion: Tropical Endemic Limbo-Conjunctivitis is certainly a common condition but has a good prognosis. However, in some cases, recurrence of manifestations can lead to complications that can impair visual function.